Deriving meteor stream properties from meteor count rate time series in a multi-observer network - J. De Keyser; S. Calders; H. Lamy; F. Verbelen; K. Kolenberg (Planetary and Space Science, 2026)

Evaluating airborne, mobile and terrestrial laser scanning for urban tree inventories: A case study in Ghent, Belgium - B. D’hont; K. Calders; H. Bartholomeus; A. Lau; L. Terryn; T.E. Verhelst; H. Verbeeck (Urban Forestry & Urban Greening, 2024)

Capturing seasonal radial growth of boreal trees with terrestrial laser scanning - T. Yrttimaa; S. Junttila; V. Luoma; K. Calders; V. Kankare; N. Saarinen; A. Kukko; M. Holopainen; J. Hyyppä; M. Vastaranta (Forest Ecology and Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Importance of Consistent Global Forest Aboveground Biomass Product Validation - L. Duncanson; J. Armston; M. Disney; V. Avitabile; N. Barbier; K. Calders; S. Carter; J. Chave; M. Herold; T. W. Crowther; M. Falkowski; J. R. Kellner; et al. (Surveys in Geophysics, 2019)

Innovations in Ground and Airborne Technologies as Reference and for Training and Validation: Terrestrial Laser Scanning (TLS) - M. Disney; A. Burt; K. Calders; C. Schaaf; A. Stovall (Surveys in Geophysics, 2019)

Presentation and analysis of a worldwide database for lava dome collapse events: the Global Archive of Dome Instabilities (GLADIS) - Claire E. Harnett; Mark E. Thomas; Eliza S. Calder; Susanna K. Ebmeier; Alison Telford; William Murphy; Jurgen Neuberg (Bulletin of Volcanology, 2019)

Torso-Tank Validation of High-Resolution Electrogastrography (EGG): Forward Modelling, Methodology and Results - Stefan Calder; Greg O’Grady; Leo K. Cheng; Peng Du (Annals of Biomedical Engineering, 2018)

Biomineralisation during operculum regeneration in the polychaete Spirobranchus lamarcki - Réka Szabó; Angus C. Calder; David E. K. Ferrier (Marine Biology, 2014)